Online hand, foot and mouth disease monitoring system - Raja Chinnappa, Munisamy (Universiti Malaysia Sarawak (UNIMAS), 2014)
When a child is suspected of having the Hand, Foot, Mouth disease (HFMD) which is a common disease that infects children below 10 years old, the doctor will give medication such as paracetamol to relieve the pain and advise the parents to quarantine their children at home until the child is cured. These doctors need to fill up forms and inform the Pusat Kesihatan Sahagian about the suspected cases they have attended. Then, the Pusat Kesihatan Sahagian will take preventive measurements after investigation on the cases that were reported by the doctors, has been done. This is where the proposed system comes in. The purpose of the Online Hand, Foot and Mouth Disease Monitoring System is to enhance the current situation to be more ejficientfor the stakeholders of the system. This system serves as a platform for the doctors to get current data equipped with a graph that is able to predict and visualize the outbreak of the disease. At the same time, doctors are able to notify the authorized personnel on recent cases and are able to update the cases they attend earlier to get the progress of the patient. Currently there is no decision making system that is created to monitor the outbreak of this disease, thus it is aimed that this system will be a proof of concept.